The Effect of Knowledge, Psychological Factors, Technology and Culture in Adopting Islamic Banking - Kumaidi; Asyari, Asyari (EKONOMIKA SYARIAH : Journal of Economic Studies, 2024)
This study was conducted to analyze the extent to which knowledge, psychological factors, technology, and culture influence the preferences of the Minangkabau community in conducting transactions with Islamic banks. The design of this research is quantitative correlational. The population in this study consists of the Minangkabau ethnic community in Bukittinggi, aged between 15 and 34 years, with a total population of 48,106 individuals. A sample size of 397 Minangkabau respondents was selected using Slovin’s formula with a critical value of 5%. The sample was determined through combination sampling to ensure the data collected represented all districts in Bukittinggi. Data were gathered through the distribution of questionnaires and analyzed using multiple linear regression analysis techniques. The results of the study indicate that knowledge has a negative but not significant effect on the intention of the community to transact with Islamic banks. Meanwhile, the variables of psychological factors, technology, and Minangkabau culture have a significant positive influence on the Minangkabau community's intention to transact with Islamic banks. Penelitian ini dilakukan untuk menganalisis seberapa besar pengaruh pengetahuan, psikologis, teknologi dan budaya terhadap preferensi masyarakat Minangkabau untuk bertransaksi di bank syariah. Bentuk penelitian ini adalah kuantitatif korelasional. Populasi dalam penelitian ini adalah masyarakat kota Bukittinggi yang beretnis Minangkabau dengan kisaran usia dari 15-34 tahun dengan jumlah populasi 48.106 orang. Dalam penelitian ini diambil jumlah sampel sebanyak 397 responden masyarakat Minangkabau yang ditentukan dengan menggunakan rumus slovin dengan nilai kritis 5%. Selanjutnya penentuan pengambilan sampel dilakukan secara combination sampling agar data yang diperoleh menyebar mewakili secara area sampling kesetiap kecamatan yang ada di Bukittinggi. Data dikumpulkan melalui metode penyebaran angket kuisioner yang kemudian dianalisis dengan teknik analisis regresi linier berganda. Hasil penelitian menunjukan bahwa pengetahuan berpengaruh negatif namun tidak signifikan terhadap intensi masyarakat untuk bertransaksi di bank syariah. Sedangkan variabel Psikologis, Teknologi dan Budaya Minangkabau mempunyai pengaruh yang positif signifikan terhadap intensi masyarakat Minangkabau untuk bertransaksi di bank syariah.